2021
DOI: 10.1002/art.41666
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Function of Tumor Necrosis Factor and Interleukin‐6–Induced Osteoclasts in Rheumatoid Arthritis

Abstract: Objective We have previously reported that stimulation of mouse bone marrow–derived macrophages with tumor necrosis factor (TNF) and interleukin‐6 (IL‐6) induces differentiation of osteoclast‐like cells. We undertook this study to clarify the characterization and function of human TNF and IL‐6–induced osteoclasts using peripheral blood collected from patients with rheumatoid arthritis (RA) and healthy donors. Methods Peripheral blood monocytes were cultured with a combination of TNF and IL‐6, TNF alone, IL‐6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 34 publications
(43 reference statements)
2
60
0
1
Order By: Relevance
“…Interestingly, whereas bone absorption activity cannot be abolished in mice with STAT3 conditional knockout, treatment with JAK inhibitor or MEK inhibitor achieves this [104]. Furthermore, the number of osteoclasts induced ex vivo from RA patient PBMCs with TNF and IL-6 is positively correlated with the host patient modified total Sharp score [105]. IL-17 A also promotes MMP production in chondrocytes [106].…”
Section: Rankl Regulation By Cytokinesmentioning
confidence: 99%
“…Interestingly, whereas bone absorption activity cannot be abolished in mice with STAT3 conditional knockout, treatment with JAK inhibitor or MEK inhibitor achieves this [104]. Furthermore, the number of osteoclasts induced ex vivo from RA patient PBMCs with TNF and IL-6 is positively correlated with the host patient modified total Sharp score [105]. IL-17 A also promotes MMP production in chondrocytes [106].…”
Section: Rankl Regulation By Cytokinesmentioning
confidence: 99%
“…(55,56) Accordingly, Huck et al (57) found that deletion of Rac1, exclusively at preosteoblastic stage, leads to decreased osteoblast proliferation and increased apoptosis, and in vivo deletion of Rac1 in mice results in decreased histomorphometric measures of osteoblast function, osteoid thickness, and BMD, which could be mediated through WNT signaling, as demonstrated by Wan et al (58) Because macrophages are an important source of inflammatory cytokines, it is also possible that some of the ARHGAP25 variant's negative effects on bone homeostasis could be indirect and mediated by abnormal production of such cytokines. (59) The skeletal phenotype of the Finnish family reported here could, therefore, result from defects in both osteoclast and osteoblast function.…”
Section: Discussionmentioning
confidence: 84%
“…Yokota et al, have recently shown that the TNF-α treatment of human peripheral monocytes induced abundant TRAP-positive cells despite only a few multinucleated cells compared with the RANKL treatment [ 37 ]. In contrast, TNF-α-induced osteoclast-like macrophages highly expressed MMP3 mRNA compared with RANKL-induced osteoclasts.…”
Section: Discussionmentioning
confidence: 99%